2004
DOI: 10.1682/jrrd.2003.04.0060
|View full text |Cite
|
Sign up to set email alerts
|

The influence of voluntary tonic EMG level on the vestibular-evoked myogenic potential

Abstract: Vestibular-evoked myogenic potentials (VEMPs) are proposed as a reliable test to supplement the current vestibular test battery by providing diagnostic information about saccular and/or inferior vestibular nerve function. VEMPs are short-latency electromyograms (EMGs) evoked by high-level acoustic stimuli and recorded from surface electrodes over the tonically contracted sternocleidomastoid muscle. VEMP amplitude is influenced by the EMG level, which must be controlled. This study examined the ability of subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
119
3
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(132 citation statements)
references
References 29 publications
7
119
3
3
Order By: Relevance
“…Alternatively, the muscle tone may be quantified in terms of the pre-stimulus root-mean-square (RMS) value of the sEMG, which was reported to be linearly related to the VEMP amplitude as well (Lim et al, 1995). Subsequent studies corroborated these findings (Ochi et al, 2001;Welgampola et al, 2003;Akin et al, 2004). Nowadays, the prevailing idea seems to be that the VEMP amplitude is proportional to the sEMG level.…”
Section: Introductionmentioning
confidence: 67%
“…Alternatively, the muscle tone may be quantified in terms of the pre-stimulus root-mean-square (RMS) value of the sEMG, which was reported to be linearly related to the VEMP amplitude as well (Lim et al, 1995). Subsequent studies corroborated these findings (Ochi et al, 2001;Welgampola et al, 2003;Akin et al, 2004). Nowadays, the prevailing idea seems to be that the VEMP amplitude is proportional to the sEMG level.…”
Section: Introductionmentioning
confidence: 67%
“…Regarding the acoustic stimulus, a variety of frequencies have been described. However, frequencies equal to or below 5 Hz are the most often used and evoke more homogeneous, constant responses.. 5,8,9,21 Response characteristics depend upon the type of stimulus administered. According to a number of studies, vestibular myogenic potentials evoked by tone bursts require a lower stimulation threshold than evocation by clicks.15,22 Placement of the electrodes on the surface of the SCM muscle has been the most often employed method, for, according to the literature, the responses are more consistent and homogeneous; it is also a more practical method for the examiner and more comfortable for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…The calculation of the asymmetry index indicated variation ranging from 0.2 to 26.4%, which, based on previously published normality data, is considered adequate. [8][9][10][11] The findings on the participant over 60 years of age should be discussed, as previous studies have found significant differences in the VEMP amplitude values in elderly individuals. These differences occur due to the ageing of the saccular macula and muscle fibers.10 However, this was not found in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both can be done with the patient either in a sitting or a supine position. The neck flexion method has several variations and SCM muscle activation is achieved by lifting the head against gravity in the supine position or by pushing the head forward against a padded bar whilst in the sitting position (Ozdek et al, 2009;Akin et al, 2004;Welgampola & Colebatch, 2005). Isaacson and colleagues (2006) compared three methods of SCM muscle activation and found that eliciting cVEMPs with the subject in the supine position with the head turned to the contralateral side of stimulation leads to the most robust amplitudes.…”
Section: Vestibular Function Testing Commonly Consists Of a Battery Omentioning
confidence: 99%